Analysis of the Course of Action in Practices - Fontanille, Jacques (2016)
This is a semiotic essay in which the production of meaning is analyzed during the course of action. As it is an opened course, its nature and projective scope are relevant,whichplacesus inthe actionfieldas language, and also in the syntagmatic settings needed to maintain the congruence. In order to achieve it, the course of action would have to use adaptation, regulation, adjustment, memory and anticipation, etc. For example, there is a typology of traces which leads us from the forms to the interpretative processes, as well as to the concordance or discordance, and to the interpretation rules.